E-Commerce Development System In Improving The Stability Of Umkm In Deli Serdang, North Sumatera - Taufik Yuandika Bahri (SEAN Institute, 2023)
E-Commerce is one of the latest ways that many people are interested in to sell brand merchandise because it provides convenience but the effect of this convenience also results in the emergence of an unhealthy competition between sellers to attract consumer attention. This study aims to determine the effect of perceived usefulness, perceived convenience, attitudes, behavioral interests, and behavioral control on the use of e-commerce in Medan city. The type of data used in this study is to use primary data obtained from respondents directly using a questionnaire. The population in this study amounted to 150 traders and a sample of 60 clothing and accessories traders The results showed that the behavioral interest variable (X4) had a partially positive and significant effect on the use of e-commerce (Y), the attitude variable (X3) had a partially positive and insignificant effect on the use of e-commerce (Y), and the remaining variables, namely, perceived usefulness (X1), perceived convenience (X2), and behavioral control (X5) had no partial effect on the use of e-commerce (Y). the determination test results of the study were 0.311 (31.1%) and the remaining 68.9% was explained by other factors or variables not included in this study. However, all the independent variables in this study have a significant effect simultaneously on the dependent variable.